Prosedur Penyusutan Arsip Pada BPJS Ketenagakerjaan Cabang Banda Aceh - Alghifari, Muhammad Dzar; Aini, Zahriatul (Jurnal EMT KITA, 2024)
The archives are one of the important sources of information that can support the processes of administrative and bureaucratic activities. The archives created from processing units will always be improved because the activities of an institution or individual never stop and will grow. One way to reduce the amount excess archives in an organization or agency is by narrowing the archives. Archive reduction is one of the activities of archive management in the archival unit of an institution such as BPJS Ketenagakerjaan Banda Aceh Branch. The purpose of this research is to find out the stages of archive narrowing, and the constraints experienced by the BPJS of Banda Aceh Branch. This research uses qualitative descriptive methods with observational data collection techniques, interviews, and library studies. The result of this research is the production of archive shrinkage in BPJS. The archive is destroyed by the Archival Unit in several ways, and the archive transfer is carried out by the Archival Unit to the Head of ANRI. The transfer of archives to BPJS is done according to the guidelines of JRA. The problems experienced by BPJS are limited archive storage, a lack of human resources, and a lack of training for human resources.